2010
DOI: 10.1002/dvdy.22395
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of nectin‐1 and nectin‐3 is required for normal ameloblast function and crown shape development in mouse teeth

Abstract: Nectins are immunoglobulin-like cell adhesion proteins and their interactions recruit various cell-cell junctions. Mutations in human NECTIN-1 cause an ectodermal dysplasia syndrome, but Nectin-1 null mice have only slight defects in teeth, suggesting compensation by other nectin(s). We observed overlapping expression of nectin-3 with nectin-1 and enamel abnormality in the nectin-3 mutant. We, therefore, generated nectin-1;nectin-3 compound mutants. However, all teeth developed and no significant dental abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 48 publications
1
48
0
2
Order By: Relevance
“…2A, C ;Hu et al, 2005). This stratum intermedium plays an essential role in the functional differentiation of ameloblasts (Lesot & Brook, 2009;Nait Lechguer et al, 2011;Yoshida et al, 2010). Only in one report, non polarized ameloblasts-like cells expressing amelogenin appeared to be generated in the absence of a stratum intermedium (Honda & Hata, 2010).…”
Section: Fig 2 Histology Of Dental Epithelial and Mesenchymal Cell-mentioning
confidence: 99%
“…2A, C ;Hu et al, 2005). This stratum intermedium plays an essential role in the functional differentiation of ameloblasts (Lesot & Brook, 2009;Nait Lechguer et al, 2011;Yoshida et al, 2010). Only in one report, non polarized ameloblasts-like cells expressing amelogenin appeared to be generated in the absence of a stratum intermedium (Honda & Hata, 2010).…”
Section: Fig 2 Histology Of Dental Epithelial and Mesenchymal Cell-mentioning
confidence: 99%
“…Hence, nectin-1 null mutant mice do not recapitulate the phenotypes of human CLPED1 and they cannot be used as an appropriate animal model to examine the pathogenesis of CLPED1 or the role of nectins in the morphogenesis of ectodermal organs. As previous studies have reported that overlapping expression of nectins in skin and nectins may act via heterophilic nectin-nectin interactions, we hypothesized that the function of nectin-1 may be compensated by other nectins in mice [8,24]. As the interaction between nectin-1 and nectin-3 is the strongest among nectin interactions [2] and nectin-1 and nectin-3 mutant mice have overlapping abnormalities, nectin-3 appeared as a good candidate for the compensating nectin.…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies in mouse show that nectin interactions are involved in formation and/or maintenance of desmosomes as well [7,8]. The identification of mutations in NECTIN-1 (PVRL1) gene as the cause of severe human ectodermal dysplasia (ED) syndrome Cleft Lip/Palate-Ectodermal Dysplasia Syndrome 1 (CLPED1, MIM 225060) indicates an important role for nectin in the development of mammalian skin and its appendages [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations